Development of a saline aquaponic system, integrating Oreochromis Mossambicus and Portulaca Oleracea - Bismin Shaw, S N (KUFOS, 2019)
Abstract- The study evaluates the possibility of developing a saline aquaponic system integrating Oreochromis mossambicus with Portulaca oleracea. The experimental design was completely randomized with one control and four treatments. Control(C) and each treatment had three replications. Treatments were T1, T2, T3 and T4 with salinity 5ppt, 10ppt, 15ppt and 20ppt respectively. A total number of 180 healthy Oreochromis mossambicus fry with an average weight of 2±0.033g were stocked in plastic crates of 75L capacity and fed with commercial feed having 24% crude protein. The water temperature, pH, dissolved oxygen and total ammonia levels did not show significant variations among the treatments. Growth and feed conversion is generally affected by chronically low DO concentrations below 3.5 mg/L for Tilapia. In this study, the DO level ranged between 5.0-5.67 mg/L throughout the study. The rate of evaporation in the system was very high in the case of 10, 15 and 20ppt. Adding of 10L of fresh water into the system solved that problem. The percentage of moisture was very low in the case of control (0ppt). Highest range of moisture was obtained in the treatment of 10ppt salinity. The highest value of crude protein was observed in the highest salinity of 20ppt. In the case of crude lipid, the control and treatments 1 and 2 showed low percentage of lipid, the treatment 3 (15ppt) showed the highest value. Ash content was highest for the treatment 4 (20ppt). In this experiment, the plant variety did not perform well in utilizing the nitrogen and phosphorus derivatives. A total number of 10 single colonies were isolated from each sample and conducted nitrifying bacteria activity test and selected altogether 5 isolates from all the samples which showed better nitrifying activities. No detailed studies on the isolated strains were conducted. It is noted that all the strains isolated were halotolerant.